Developing Dynamic Economic Leaders and Their Role in Achieving Competitive Advantage (International Journal of Financial, Administrative and Economic Sciences, 2024)
The current study aims to focus on developing dynamic economic leaders and defining their role in achieving competitive advantage for contemporary organizations. The study focuses on explaining the concept and importance of developing dynamic economic leaders, and its role in achieving competitive advantage in light of the contemporary world characterized by rapid economic changes and challenges. This study seeks to develop a framework that explains the relationship between developing dynamic economic leaders and achieving competitive advantage in a highly competitive business environment in the contemporary world. The study adopts the descriptive and analytical approach in addressing the theme through a review of theoretical literature and previous studies that dealt with the concept of dynamic economic leadership and its various dimensions, and the concept of competitive advantage and its components in the contemporary business environment. The researchers concluded that there is a close relationship between developing dynamic economic leaders and achieving competitive advantage in these organizations. It became clear to the researchers the importance of the relationship between the two concepts through the role that the development of dynamic economic leadership can play in serving the organization’s goals in the field of achieving and sustaining its competitive advantage. The study concluded its theoretical framework by drawing a set of conclusions and presenting a set of recommendations that would strengthen the relationship between developing dynamic economic leaders and serving the competitive advantage of organizations in the contemporary competitive business world.
Keywords: Dynamic Economic Leaders; Competitive Advantage; Competitive Business Environment; Dynamic Capabilities; Business Intelligence.